Multifunctional α-NaYbF4:Tm3+ nanocrystals with intense ultraviolet self-sensitized upconversion luminescence and highly efficient optical heating. Issue 16 (15th August 2022) - Li, Anming; Li, Xuanbo; Wang, Junli; Guo, Yansheng; Li, Chenggang; Chen, Weiguang; Wang, Zhiwen; Tang, Yanan
Abstract: Lanthanide-doped upconversion photoluminescent nanoparticles with unique anti-Stokes spectroscopic properties excel in many fields of application. Ytterbium-based self-sensitized fluorides with rich Yb 3+ possess higher absorption efficiency of incident near infrared laser, and are more favorable for photoluminescence or optical heating applications. In this work, α-NaYbF4 :Tm 3+ crystalline nanoparticles are synthesized, which exhibit intense ultraviolet self-sensitized upconversion photoluminescence and highly efficient optical heating capability under 980 nm laser excitation. NaYbF4 :Tm 3+ nanocrystals emit multi-band luminescence with emission peaks located in the ultraviolet, blue and red spectral regions. The energy transfer mechanism and electronic transition pathways for the Upconversion luminescence are investigated based on the energy level scheme, and are further confirmed by luminescent dynamic analysis. Due to cross-relaxations between Tm 3+ and energy back transfer from Tm 3+ to Yb 3+ processes, the NaYbF4 : 1 mol% Tm 3+ nanoparticles possess the highest luminescence intensity. The luminescent dynamic characteristics, such as decay time and rise time, vary with Tm 3+ doping concentrations. Highly efficient optical heating effect is observed in the NaYbF4 :Tm 3+ nanoparticles with slope efficiency of photothermal conversion for 10 s laser irradiation is as high as 100.48 °C/W.